Effectiveness of interventions to improve adverse drug reaction reporting by healthcare professionals over the last decade: A systematic review. Issue 1 (14th November 2019) - Li, Raymond; Zaidi, Syed Tabish Razi; Chen, Timothy; Castelino, Ronald
Abstract: Background: Various strategies have been studied in the literature to address the significant underreporting of adverse drug reactions (ADRs) in healthcare systems worldwide. Objectives: We conducted a systematic review of the literature that assessed the impact of various strategies to improve ADR reporting published in the last decade and compared this with the strategies identified in a previous systematic review. Methods: MEDLINE and EMBASE databases were used to retrieve papers published from 01 July 2010 to 17 June 2019. We included papers in the English language that investigated the quantitative impact of strategies used to improve ADR reporting. Results: A total of 10, 021 articles were retrieved using our search criteria, of which 13 met the inclusion criteria. Multifaceted strategies resulted in a point estimate increase in ADR reporting of 9.26‐fold (−2.21–17.11, 95% CI) versus 7.19‐fold (−5.29–32.68, 95% CI) for single interventions. Using electronic reporting tools was more commonly identified as an interventional strategy with a point estimate increase of 13.69‐fold (−5.29–32.68, 95%CI) versus 4.42‐fold (0.66–8.19, 95% CI) for traditional educational methods. The quality of the majority of publications included in this review was low. Conclusions: Developments in digital technology in the last decade has led to the increased use of electronic reporting tools to improve ADR reporting. Higher quality studies investigating the impact of these electronic methods are needed to fully explore its role in improving ADR reporting.